Community Empowerment Through Bridal Makeup Training for Wedding Center Employees in Koto Tangah District - Dewi, Siska Miga; Rani, Yati Aisya; Aulia, Fauzan (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the competencies of bridal staff through basic bridal makeup training. The program partnered with Humaira Pelaminan and Rindu Pesta, two bridal service providers located in Koto Tangah District. The training was delivered through hands-on practice, model demonstrations, mentoring, and performance evaluations. Program effectiveness was evaluated using observation sheets and performance assessment rubrics covering three competency domains: basic makeup techniques, proficiency in the use of cosmetic products, and bridal makeup aesthetics. The collected data were analyzed descriptively by comparing participants’ performance before and after the training. The results demonstrated substantial improvements in participants’ understanding of basic makeup techniques (81%), proficiency in using professional cosmetic products (76%), and application of bridal makeup aesthetics (86%). In addition, participants showed increased confidence in independently performing bridal makeup. Overall, the program effectively strengthened participants’ competencies and is expected to improve the quality of bridal services while enhancing the competitiveness of local bridal businesses in the wedding services industry.